Ibrahim El-Salahi: A Visionary Modernist - ElSalahi, Ibrahim; Hassan, Salah M. (NY; Museum for African Art, 2012)
Exhibition catalog. Contributors: Salah Hassan, Chika Okeke-Agulu, Iftikhar Dadi, Goldwin Smith. Ibrahim El-Salahi is one of the most influential figures in Sudanese modern art. Through his extraordinary artwork and remarkable writing and art criticism, he has made foundational contributions to the modernist movements in Africa and the Arab world. In his paintings, drawings, and illustrations, he engages with an array of traditional African, Arab, and Islamic visual sources as well as European art movements. His unique style transcends geographic and cultural boundaries and has inspired artists in Sudan and elsewhere in Africa for generations. El-Salahi's art offers profound possibilities for understanding African and Arab modernisms and repositioning them within the context of a broader, global modernity. This book brings together more than five decades of his work, tracing a personal journey that originates in Sudan and leads to the artist's international schooling, his detention as a political prisoner in his home country, his self-imposed exile in Qatar, and his current life in the United Kingdom.
English
Keywords: N4390-5098 Visual Arts- Exhibitions